Analisis Pengaruh Kualitas SDM, Pemahaman Akuntasi, Persepsi Pelaku UMKM, Sosialisasi SAK EMKM dan Kinerja Manajemen Terhadap Implementasi SAK EMKM: Studi Empiris pada UMKM di Kabupaten Brebes - Icha Noviasari; Lintang Kurniawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the influence of human resource quality, understanding of accounting, perceptions of MSME actors, socialization of SAK EMKM and management performance on the implementation of SAK EMKM, on MSMEs in Brebes Regency. The sampling technique used in this research was purposive sampling. A total of 100 respondents met the criteria for filling out the questionnaire. The analytical method used is moderated regression analysis. The research results provide relevant evidence that the quality of human resources and socialization of SAK EMKM have no effect on the implementation of SAK EMKM. Meanwhile, understanding accounting, perceptions of MSME actors and management performance influence the implementation of SAK EMKM.